2004
DOI: 10.1136/bmj.38272.478438.55
|View full text |Cite|
|
Sign up to set email alerts
|

Population based randomised controlled trial on impact of screening on mortality from abdominal aortic aneurysm

Abstract: Objective To assess whether screening for abdominal aortic aneurysms in men reduces mortality. Design Population based randomised controlled trial of ultrasound screening, with intention to treat analysis of age standardised mortality. Setting Community based screening programme in Western Australia. Participants 41 000 men aged 65-83 years randomised to intervention and control groups. Intervention Invitation to ultrasound screening. Main outcome measure Deaths from abdominal aortic aneurysm in the five years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
178
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(186 citation statements)
references
References 17 publications
5
178
1
2
Order By: Relevance
“…The study population was drawn from the Health In Men Study (27,28), which arose from a randomized population-based trial of ultrasound screening for abdominal aortic aneurysm in men ages 65-83 living in Perth, Western Australia. A total of 41,000 men were identified via the electoral roll (voting is compulsory in Australia) and randomized into invited and control groups of equal size.…”
Section: Methodsmentioning
confidence: 99%
“…The study population was drawn from the Health In Men Study (27,28), which arose from a randomized population-based trial of ultrasound screening for abdominal aortic aneurysm in men ages 65-83 living in Perth, Western Australia. A total of 41,000 men were identified via the electoral roll (voting is compulsory in Australia) and randomized into invited and control groups of equal size.…”
Section: Methodsmentioning
confidence: 99%
“…We also acknowledge that differential survival could have biased the results of the study, as men who were overweight or obese in mid-life might have died of competing diseases before reaching older age [21], so that surviving overweight and obese older men might be unusually healthy compared with their normal weight counterparts. We have previously reported that HIMS participants have lower mortality hazard than men who were invited but chose not to participate, and men in the general population who were not invited [22]. This suggests that HIMS participants are healthier than other men of their age living in the community, so that caution is required when attempting to generalize our findings.…”
Section: Limitations Of the Study Designmentioning
confidence: 72%
“…36 Average baseline diameters and growth rates reported in the Western Australia screening study, 37 MASS,…”
Section: Growth Rates Of Small Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…Furthermore, it was the only cardiovascular outcome for which the association with higher pulse pressure was reversed (HR 0.91, 95% CI 0.86 to 0.98). 36 However, mean baseline BP levels reported in several large AAA surveillance studies 7,19,22,37 (Table 2) are all above what is currently considered as controlled (< 140/90 mmHg 45 ) and the AAA growth rates observed in these studies (see Table 1) may at least in part be related to these higher BPs.…”
mentioning
confidence: 96%